Development of a primary melanoma in situ within a full-thickness skin graft overlying a free muscle flap: a case report. Issue 1 (1st January 2018) - Dabek, Robert J.; Baletic, Nemanja; McUmber, Harrison; Nahed, Brian; Haynes, Alex; Eberlin, Kyle R.; Bojovic, Branko
Abstract: The development of a primary melanoma within the confines of free tissue transfer is a rare occurrence. In this report, we describe the development of a primary melanoma in situ within a full-thickness skin graft overlying a free latissimus dorsi muscle flap used to cover a scalp defect.